Age-based Predictive Model of the Pediatric Ribcage - Holcombe Sven; Kindig Matthew; Zhang Peng; Parenteau Chantal; Rabban Patrick; Hully Lucy; Wang Stewart (International Journal of Automotive Engineering, 2014)
Ribcage geometry of 327 boys and girls (aged 1-18) was extracted from CT scans, consisting of three dimensional curves fit through the centroidal path of 6306 individual ribs. Each rib was characterized by 7 parameters describing a rib's in-plane geometry, 2 describing its out-of-plane deviation, and 3 describing the rib orientation relative to anatomical planes. Parameters were predicted by age and gender to fully describe variation in size and shape of rib centroidal geometry as a continuous function following growth throughout childhood. A demographics-based model was also presented describing average ribcage geometry for children of any given age, weight, and height.